Competency Upgrading for Coaches of Depok City: Internalization of Basic Characters in Sports - Kurnia Tahki; Nur Ali; Hermanto (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Based on data from the Research and Development Division of the Depok City KONI, until 2020 there were only 43.1% of Depok City coaches had sports branch certificates as legathe lization of competent coaches. This competency upgrading training aims to provide training on character competencies that are not usually discussed specifically in sports so far. The training participants are the coaches of Depok City and its surroundings who have handled 125 junior or beginner-level athletes. The training material contains basic characteristics (honesty, discipline, and cooperation) that sports coaches need to toer to internalize positive values ​​so that the coach can become a "character role model" for his athletes. Based on the results of the training, it is known that most of the coaches have high / good interest, understanding, and analysis ability in participating in this competency upgrading training (interest is 99.2%, understanding is 80%, and alyticallity is 84%). There were no differences in coaches' interests, understanding, and analysis ability in terms of gender, age, and training experience. The results of this training provide important feedback for conducting competency upgrading training in Depok City in the future.